2021
DOI: 10.1016/j.jse.2020.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Comparing internal fixation constructs for scapular spine insufficiency fractures following reverse shoulder arthroplasty

Abstract: Introduction: There is limited research on the surgical management techniques for scapular spine fractures after reverse shoulder arthroplasty (RTSA). As such, the purpose of this in vitro biomechanical study was to compare 4 fixation constructs to stabilize scapular spine insufficiency fractures. Methods: Twelve paired fresh-frozen cadaveric scapulae (N ¼ 24) were randomized into 4 fixation groups: subcutaneous border plating (AE hook) and supraspinatus fossa plating (AE hook). A Levy type II fracture was sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…More recently, Ting et al could demonstrate that subcutaneous border plating is biomechanically superior to plating in the supraspinatus fossa [ 22 ]. Both studies evaluated measures for additional fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ting et al could demonstrate that subcutaneous border plating is biomechanically superior to plating in the supraspinatus fossa [ 22 ]. Both studies evaluated measures for additional fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Another biomechanical study, by Ting et al, reported that direct subcutaneous plating of the scapular spine is more stable than supraspinatus fossa plating. 38 In our cohort, the patients achieved good results concerning range of motion after operative treatment. 13 17 In only one case, the patient had a slightly limited range of motion and mild pain.…”
Section: Discussionmentioning
confidence: 54%
“…Within the identified cohort of 18 fractures, one was classified as a Levy Type I fracture [ 16 ], 10 were Levy Type II fractures [ 17 , 30 , 31 , 32 , 33 ], and the remaining 7 fractures were defined as Levy Type III [ 18 , 29 , 34 ]. Fractures were classified according to Levy et al in two studies (four fractures) [ 13 , 17 , 19 , 34 ], with Levy classification ascertained by the authors for the other seven studies.…”
Section: Resultsmentioning
confidence: 99%
“…Positioning of the plates has also been investigated and it has been shown that plates can be placed superiorly (along the supraspinatus fossa), posteriorly (along the scapular spine) or caudally (along the infraspinatus fossa) [ 13 , 25 , 26 , 35 ]. For single plating, applying the plate over the posterior aspect of the scapular spine might be the strongest option [ 13 ]. When dual plating is performed, placing the plates over the posterior and caudal aspect of the scapular spine might provide the strongest fixation [ 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation